Current status and future prospects of stem cell therapy in Alzheimer’s disease - Zhang, Fu-Qiang (Neural Regen Res, 2019)
Alzheimer’s disease is a common progressive neurodegenerative disorder, pathologically characterized by the presence of β-amyloid plaques and neurofibrillary tangles. Current treatment approaches using drugs only alleviate the symptoms without curing the disease, which is a serious issue and influences the quality of life of the patients and their caregivers. In recent years, stem cell technology has provided new insights into the treatment of neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Currently, the main sources of stem cells include neural stem cells, embryonic stem cells, mesenchymal stem cells, and induced pluripotent stem cells. In this review, we discuss the pathophysiology and general treatment of Alzheimer’s disease, and the current state of stem cell transplantation in the treatment of Alzheimer’s disease. We also assess future challenges in the clinical application and drug development of stem cell transplantation as a treatment for Alzheimer’s disease.